Impacts of perfect fluid dark matter on spacetime geometry: the exponential metric - Jan Kuncewicz (European Physical Journal C: Particles and Fields)
Abstract Astrophysical observations provide compelling evidence for the existence of dark matter, a non-luminous component dominating the universe’s mass-energy budget. Its gravitational influence is well-established on galactic scales; however, dark matter’s precise nature and effect on spacetime geometry remain open questions. This study investigates modifications to the Schwarzschild metric due to the presence of dark matter, modeled as a perfect fluid with a specific equation of state. We derive an “exponential” metric incorporating this dark matter contribution and calculate its key characteristics: the event horizon, innermost stable circular orbit (ISCO), and photon sphere. Comparing these with Schwarzschild predictions reveals distinct deviations dependent on the dark matter distribution. Furthermore, we analyze the orbital velocity profiles derived from the exponential metric, demonstrating its potential to explain the observed flat rotation curves of galaxies. Our results underscore the importance of considering modified metrics in accurately describing spacetime near massive objects and provide a theoretical framework for further investigations into dark matter’s role in galactic dynamics.